Trend Assessments for Selected Air Quality Monitoring Stations in Turkey - Eyüp Şişman (Doğal Afetler ve Çevre Dergisi)
Numerous data collected from engineering, economy, health and social sciences activities are analyzed by trend test methods. After analyzing the data, information about the trend is gathered leading to increasing and / or decreasing trends cases. As a result, intensive efforts are being made to determine the plan for each area's unique problems and solutions in the light of all this information. It is necessary to protect the environment and to ensure that all activities in these areas are sustainable. In this study, the trend in the stations data around the coal-fired power plants is determined by the Innovative Trend Diagram (ITD). With ITD, it is tried to reveal the change in the future air quality trend or health risk. At the end of this analysis, graphics, information and comments are produced for the administrations, non-governmental organizations, experts and stakeholders. If the trend of air pollutant emissions can be explained by the visual graphs, it will be possible to reveal the air quality related risk analyzes and measures in a more concrete way. It has been determined that the air quality of Zonguldak (Center), Kahramanmaraş (Center), Çanakkale (Center, Biga, Çan), Adana (Çatalan, Doğankent, Valilik), Hatay (İskenderun), Manisa (Center), Ankara (Sincan), Kütahya and Şırnak has improved over time. At the same time, Kahramanmaraş (Elbistan), Hatay (Antakya), Muğla (Yatağan) and Manisa (Soma) air quality has deteriorated over time. It is clear that further efforts are necessary in order to be able to reach the target conditions of good quality in the air quality.